Lithium-based ceramic pre-sintered powder and preparation method thereof
By using alcohol solvents and direct prefixing after drying in the preparation process of lithium-based ceramic prefixing powder, the problem of insufficient sintering activity of lithium-based ceramic prefixing powder is solved, and the grains of prefixing powder are small and uniform. and sintering activity improves the performance and service life of the material.
Patent Information
- Application Number
- CN202411680685.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-14
AI Technical Summary
Lithium-based ceramic prefixing powder is prone to oversintering during the prefixing process, resulting in the impact of material properties and insufficient sintering activity in the prior art.
After mixing alcohol solvents with raw materials, grinding is performed to form a slurry, and pre-firing is directly performed after drying, retaining a loose and porous structure and avoiding grain connections, thereby improving sintering activity.
The lithium-based ceramic pre-fired powder obtained by this method has the characteristics of small grains, good dispersion, and better sintering activity, which reduces the risk of oversintering during subsequent sintering and improves the density and service life of the material.
Smart Images

Figure CN119430932A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of lithium-based ceramic production, and specifically relates to a lithium-based ceramic pre-fired powder and a preparation method thereof. Background Art
[0002] Lithium-based ceramics represented by garnet-type (LLZO) solid electrolytes have high ionic conductivity and are stable to lithium metal. They are one of the most popular solid electrolyte materials at present. They can be used in all-solid-state batteries and lithium extraction, and have great application prospects.
[0003] In the production process of lithium-based ceramics, the pretreatment of raw materials is one of the key factors in the preparation of high-quality solid electrolyte materials. Lithium-based ceramic pre-fired powder has a great influence on the performance of lithium-based ceramic materials obtained by subsequent sintering. The lithium-based ceramic pre-fired powder prepared in related technologies is generally prepared in order to fully eliminate the volatile components produced by the decomposition of the raw materials, resulting in partial sintering during the pre-fired process, reduced sintering activity, and thus over-sintering in the subsequent sintering process, affecting the performance of lithium-based ceramic materials.
[0004] Therefore, it is necessary to provide a sintering method for improving the sintering activity of lithium-based ceramic sintered powder. Summary of the Invention
[0005] In view of this, the present application provides a lithium-based ceramic pre-fired powder and a preparation method thereof, aiming to provide a lithium-based ceramic pre-fired powder with good sintering activity.
[0006] In a first aspect, the present application provides a method for preparing lithium-based ceramic pre-fired powder, comprising the following steps:
[0007] Step S1: providing raw materials according to the stoichiometric ratio of lithium-based ceramics;
[0008] Step S2: mixing the raw materials with an alcohol solvent and grinding them to obtain a slurry;
[0009] Step S3: drying the slurry and then directly pre-firing it to obtain lithium-based ceramic pre-firing powder.
[0010] Based on the present application, by mixing the raw materials with alcohol solvents, since the alcohol solvent has good dispersibility for the raw materials, the viscosity of the slurry after grinding and the particle size of the raw materials can be reduced, which is beneficial to reducing the grain size of the lithium-based ceramic pre-fired powder; at the same time, the slurry is dried and directly pre-fired. Compared with the related art in which the slurry is dried and then crushed and then pre-fired, the ground raw materials are evenly dispersed in the slurry, and the drying volatilizes the alcohol solvent, so that the raw materials can be relatively independent and form a loose and porous structure. Direct pre-fired can retain the loose and porous structure after the slurry is dried, and the relatively independent raw materials are not easy to be connected during the pre-fired process, thereby inhibiting grain growth and obtaining lithium-based ceramic pre-fired powder with fine and uniform grains and good dispersion. Therefore, the lithium-based ceramic pre-fired powder has good sintering activity; on the other hand, the loose and porous structure is also beneficial to the removal of volatile components generated by the raw materials during the pre-fired process, promotes the pre-fired reaction of the raw materials, further improves the sintering activity of the lithium-based ceramic pre-fired powder, and reduces the influence of volatile components generated in the subsequent sintering process on the density of the lithium-based ceramic material. In summary, the lithium-based ceramic pre-fired powder obtained by this method has fine and uniform grains, good dispersion, and good sintering activity.
[0011] It is understandable that the traditional method of crushing the slurry after drying will destroy the loose porous structure produced by the volatilization of the alcohol solvent, and the particles of the raw materials after grinding will accumulate together, which is not conducive to the removal of volatile components produced by the raw materials during the pre-firing process. In addition, material exchange is likely to occur between the raw materials, resulting in the phenomenon that some grains fuse into large grains, and the grain size is uneven. The present application directly performs pre-firing pretreatment after drying, which can effectively improve the above problems.
[0012] It should be noted that, in the context of this application, connection refers to the material exchange between raw material particles after contact after grinding, the fusion of multiple particles into a single large grain, or the generation of a similar network structure due to incomplete fusion.
[0013] In some embodiments, in step S1, the lithium-based ceramic is selected from any one of the substances represented by Formula 1;
[0014] Li 7-x La3Zr 2-x M x O 12 Formula 1
[0015] Wherein, M is a doping element, and M is selected from at least one of Ta, Nb, W, and Ti, preferably Ta; the value range of x is: 0.4≤x≤0.8, preferably 0.6.
[0016] In some of the above embodiments, the lithium-based ceramic is an LLZO-based solid electrolyte, which has high ionic conductivity and is stable to lithium metal. By doping the element M, the LLZO-based solid electrolyte can maintain a cubic phase at room temperature, and has higher ionic conductivity than the tetragonal LLZO-based solid electrolyte.
[0017] In some embodiments, the raw materials include a lithium source, where the mass of the lithium element in the lithium source is denoted as m, and the theoretical amount of lithium element is denoted as m0, satisfying 1.1m0≤m≤1.2m0. Based on the above embodiment, since lithium ions or lithium oxides readily volatilize during the pre-firing process, a moderate excess can improve the stability of the composition and structure of the lithium-based ceramic, thereby improving the physical and chemical properties of the lithium-based ceramic.
[0018] In some embodiments, the raw materials further include a La source, a Zr source, and a doping element M source.
[0019] In some embodiments, the Li source includes at least one of lithium carbonate, lithium nitrate, and lithium hydroxide, preferably lithium carbonate.
[0020] In some embodiments, the La source includes at least one of lanthanum oxide, lanthanum hydroxide, and lanthanum nitrate, preferably lanthanum hydroxide.
[0021] In some embodiments, the Zr source includes at least one of zirconium oxide, zirconium hydroxide, and zirconium nitrate, preferably zirconium oxide.
[0022] In some embodiments, the doping element M source is a Ta source, and the Ta source includes one of tantalum oxide, tantalum hydroxide, and tantalum nitrate, preferably tantalum oxide. Other doping element M sources are also typically selected from one of the oxides, hydroxides, and nitrates corresponding to the respective elements.
[0023] In some embodiments, in step S2, the alcohol solvent includes at least one of methanol, ethanol, and propanol; and the mass ratio of the raw material to the alcohol solvent is 0.2 to 0.7:1. For example, the mass ratio of the raw material to the alcohol solvent is any one of 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, or any range thereof. In some examples, the mass ratio of the raw material to the alcohol solvent is 2:7, 3:7, or 4:6. Preferably, the mass ratio of the raw material to the alcohol solvent is 0.4 to 0.5:1. In some examples, the mass ratio of the raw material to the alcohol solvent is 3:7.
[0024] In some of the above embodiments, the alcohol solvent can better disperse the raw materials, which is more conducive to obtaining raw materials with smaller particle size. At the same time, the appropriate mass ratio is also conducive to obtaining a loose and porous structure after drying, thereby further avoiding grain bonding, reducing grain size, and improving dispersibility. The obtained lithium-based ceramic pre-fired powder has better sintering activity.
[0025] As an example, Figure 1 This is a particle size distribution diagram of the raw materials in the slurry in one embodiment of the present application, Dv10 = 0.301 μm, Dv50 = 0.425 μm, Dv90 = 0.589 μm, indicating that using an alcohol solvent as a solvent to disperse the raw materials and then grinding them can control the Dv50 of the raw materials in the material to below 0.5 μm.
[0026] In some embodiments, in step S2, the Dv50 of the raw materials in the slurry is less than 0.5 μm. Based on the above embodiment, by grinding the raw materials in the slurry to meet the above requirements, the grain size can be further refined, the dispersibility can be improved, and the sintering activity of the lithium-based ceramic pre-fired powder can be improved.
[0027] In some embodiments, the grinding process includes: grinding at 1500-2500 r / min using a grinder, where the grinder may be a sand mill, or other suitable grinding methods.
[0028] In some embodiments, in step S3, directly pre-firing the slurry after drying it includes: placing the slurry in a magnesium oxide crucible, drying it, and then directly pre-firing it. Based on the above embodiment, the magnesium oxide crucible is used as a reaction container for both the drying and pre-firing processes. This can prevent aluminum ions in a traditional alumina crucible from being transferred through the crucible to the ceramic pre-firing powder. Aluminum ions can replace lithium ions in the ceramic pre-firing powder and cause contamination to lithium-based ceramics. Therefore, using a magnesium oxide crucible can reduce impurities in the lithium-based ceramic pre-firing powder.
[0029] In some embodiments, in step S3, the liquid level of the slurry in the magnesium oxide crucible does not exceed 10 mm. Based on the above embodiment, under this condition, the volatile components generated by the raw materials at the bottom layer during the pre-sintering process can be fully removed, further improving the sintering activity of the lithium-based ceramic pre-sintered powder.
[0030] In some embodiments, in step S3, the drying conditions include: drying temperature: 70° C. to 90° C.; drying time: 600 min to 800 min.
[0031] In some of the above embodiments, by drying under the above conditions, a suitable drying speed is more conducive to the full volatilization of the solvent in the slurry, forming a loose and porous structure, thereby further avoiding grain bonding, reducing grain size, improving dispersibility, and obtaining a lithium-based ceramic pre-fired powder with better sintering activity. For example, the drying temperature can be any value of 70°C, 72°C, 75°C, 78°C, 80°C, 85°C, 88°C, 90°C or any range of the above two; the drying time can be any value of 600min, 620min, 630min, 640min, 650min, 680min, 700min, 720min, 750min, 780min, 800min or any range of the above two.
[0032] In this process, the drying temperature is 70°C to 90°C, and the drying time is 600min to 800min. In addition to forming a better loose porous structure, it can also ensure safety and achieve higher drying efficiency, making the drying time more appropriate.
[0033] In some embodiments, in step S3, the conditions for the pre-calcination treatment include: heating to 390-410°C and keeping warm for 60-550 minutes, then heating to 640-660°C and keeping warm for 60-550 minutes, then heating to 710-730°C and keeping warm for 60-550 minutes, then heating to 760-770°C and keeping warm for 60-550 minutes, then heating to 910-930°C and keeping warm for 300-800 minutes.
[0034] In some of the aforementioned embodiments, staged pre-firing allows for the full physical and chemical reactions in the raw materials to proceed, further eliminating volatile components produced by raw material decomposition. This reduces the risk of pores in the pre-firing lithium-based ceramic powder, which may adversely affect the density of the lithium-based ceramic material during subsequent sintering. Of particular note, staged pre-firing can further reduce the intergranular connectivity and grain size.
[0035] It is understandable that in the traditional method of directly heating the material to the target temperature for pre-firing, various physical and chemical reactions in the raw materials occur simultaneously, which may lead to insufficient pre-firing reaction at low temperature, and partial sintering of the raw materials may occur at high temperature for a long time, both of which are not conducive to obtaining lithium-based ceramic materials with better performance. The use of segmented pre-firing treatment can effectively reduce the occurrence of the above problems; on the other hand, segmented pre-firing is also conducive to the segmented elimination of volatile components decomposed from the raw materials, and the elimination effect is better than the traditional method of directly heating the material to the target temperature for pre-firing.
[0036] As an example, in one embodiment of the present application, the raw materials are lithium carbonate, lanthanum hydroxide, zirconium oxide, and tantalum oxide. The differential thermal gravimetric curve of the raw materials is as follows: Figure 2 As shown, it indicates that physical and chemical reactions occur at 380℃, 480℃, 550℃, 650℃, 720℃, and 770℃, respectively. The physical and chemical reactions may include the following reactions:
[0037] (LaCOH contains multiple crystal forms and needs to be decomposed in sequence at 480℃, 550℃, and 650℃).
[0038]
[0039] Further preferably, in some embodiments, in step S3, the conditions of the pre-calcination treatment include: heating to 390-410°C and keeping warm for 120-480 minutes, then heating to 640-660°C and keeping warm for 120-480 minutes, then heating to 710-730°C and keeping warm for 120-480 minutes, then heating to 760-770°C and keeping warm for 120-480 minutes, then heating to 910-930°C and keeping warm for 300-600 minutes.
[0040] Further preferably, the temperature is raised to 390-410°C, and the holding time is selected from any value of 120min, 150min, 180min, 200min, 240min, 280min, 300min, 360min, 400min, 420min, 480min or any range thereof; the temperature is raised to 640-660°C, and the holding time is selected from any value of 120min, 150min, 180min, 200min, 240min, 280min, 300min, 360min, 400min, 420min, 480min or any range thereof;
[0041] The temperature is raised to 710-730°C, and the holding time is selected from any value of 120 min, 150 min, 180 min, 200 min, 240 min, 280 min, 300 min, 360 min, 400 min, 420 min, 480 min, or any range thereof;
[0042] The temperature is raised to 760-770°C, and the holding time is selected from any value of 120 min, 150 min, 180 min, 200 min, 240 min, 280 min, 300 min, 360 min, 400 min, 420 min, 480 min, or any range thereof;
[0043] The temperature is raised to 910-930°C, and the holding time is selected from any value among 300min, 360min, 420min, 480min, 540min, 600min or any range among the above two values.
[0044] In the present application, during the staged pre-firing process, the corresponding holding times at different temperatures are selected independently.
[0045] In some of the above-mentioned embodiments, the holding time at each temperature range during the pre-sintering process is further limited. Under these conditions, the pre-sintering reaction of the raw materials at different temperatures can be fully carried out, the phenomenon of partial sintering caused by excessive holding time can be reduced, and the fusion of small grains in the pre-sintered powder into larger grains can be inhibited. As a result, the resulting lithium-based ceramic pre-sintered powder has finer, more uniform, and better dispersed grains, and has better sintering activity. Under these conditions, the grain size of the obtained lithium-based ceramic pre-sintered powder can be 1 to 3 μm.
[0046] In some embodiments, the heating rates during the pre-calcination process are each independently 3°C / min to 10°C / min. Based on the above embodiments, when the heating rates in each temperature range during the pre-calcination process meet the above conditions, the target temperature range can be reached quickly, pre-calcination efficiency is improved, sintering is reduced, and the resulting pre-calcined powder has better sintering activity.
[0047] In a second aspect, the present application provides a lithium-based ceramic pre-fired powder, which is prepared according to the method described in any embodiment of the first aspect.
[0048] According to the present application, the lithium-based ceramic pre-fired powder is obtained according to the method described in any embodiment of the first aspect, and therefore has the beneficial effects of the first aspect.
[0049] In some embodiments, the grain size of the lithium-based ceramic pre-fired powder is 0.1 to 10 μm, preferably 1 to 3 μm. Based on the above embodiment, the grain size of the lithium-based ceramic pre-fired powder is within the above range, and the lithium-based ceramic pre-fired powder has higher sintering activity.
[0050] In a third aspect, the present application also provides a method for preparing a lithium-based ceramic material, including any of the above methods for preparing lithium-based ceramic pre-fired powder.
[0051] The method for preparing the lithium-based ceramic material may further include preparing the prepared pre-calcined powder into a slurry, spray granulating the slurry to obtain lithium-based ceramic granulated powder, pressing the lithium-based ceramic granulated powder into a lithium-based ceramic green body, and sintering the lithium-based ceramic green body to obtain the lithium-based ceramic material. The lithium-based ceramic material may have a sheet structure.
[0052] For spray granulation, any suitable method in the prior art or the method provided in the present application can be used:
[0053] A method for preparing lithium-based ceramic granulated powder comprises the following steps:
[0054] Step S1: providing raw materials according to the stoichiometric ratio of lithium-based ceramics, and pre-firing to obtain lithium-based ceramic pre-firing powder, wherein the raw materials include a lithium source;
[0055] Step S2: mixing the lithium-based ceramic pre-fired powder with a composite solvent to prepare a slurry, wherein the composite solvent includes an organic solvent and water;
[0056] Step S3: spray granulating the slurry to obtain lithium-based ceramic granulated powder.
[0057] In some embodiments, in step S2, the organic solvent includes at least one of ethanol, propanol, and n-butanol; preferably, the organic solvent is ethanol.
[0058] In some embodiments, in step S2, the mass ratio of the organic solvent to water in the composite solvent is 1:2-5; preferably, the mass ratio of the organic solvent to water is 1:2.5-3.
[0059] In some embodiments, in step S2, the solid content of the slurry is 20 wt% to 70 wt%.
[0060] In some embodiments, in step S2, the pH of the slurry is 8-10.
[0061] In some embodiments, in step S3, the conditions for the spray granulation treatment include: an air inlet temperature of 130-160°C; preferably, the air inlet temperature is 145-155°C.
[0062] In some embodiments, in step S3, the conditions of the spray granulation treatment further include: introducing gas into the air inlet, wherein the gas includes an inert gas;
[0063] Preferably, the gas further comprises air;
[0064] Preferably, the volume ratio of the inert gas to air is 1:3-7;
[0065] Further preferably, the volume ratio of the inert gas to air is 1:4.5-5.5.
[0066] The sintering process may be any suitable method in the prior art, or the method provided in the present application as follows:
[0067] A method for preparing a lithium-based ceramic material comprises the following steps:
[0068] Step S1: stacking a plurality of lithium-based ceramic green sheets in a thickness direction and placing them in a first crucible with a first lithium-based ceramic pre-fired powder on the bottom, wherein a second lithium-based ceramic pre-fired powder is sprinkled between the plurality of lithium-based ceramic green sheets;
[0069] Step S2: placing the second crucible upside down into the first crucible with its opening facing downward, so that the plurality of lithium-based ceramic green compacts are accommodated in the second crucible;
[0070] Step S3: sealing the first crucible containing the second crucible with a crucible cover and then performing a sintering process to sinter the lithium-based ceramic green body to obtain the lithium-based ceramic material.
[0071] In some embodiments, the total height h of the plurality of lithium-based ceramic green sheets stacked in the thickness direction and the height H of the second crucible satisfy the following conditions: 0.3H≤h<H;
[0072] Preferably, 0.5H≤h<H;
[0073] Further preferably, 0.7H≤h<H;
[0074] Still more preferably, 0.9H≤h<H.
[0075] In some embodiments, the total height h of the plurality of lithium-based ceramic green sheets stacked in the thickness direction and the height H of the second crucible satisfy: 0.5H≤h<H; and,
[0076] When the height h1 of a lithium-based ceramic green body after stacking several lithium-based ceramic green bodies satisfies 0.3H≤h1<0.7H, the density of the lithium-based ceramic material obtained by sintering the green body is 96% to 97%;
[0077] When the height h1 of a lithium-based ceramic green body after stacking several lithium-based ceramic green bodies satisfies 0.7H≤h1<0.9H, the density of the lithium-based ceramic material obtained by sintering the green body is 97% to 99%;
[0078] When the height h1 of a lithium-based ceramic green body after a plurality of lithium-based ceramic green bodies are stacked satisfies 0.9H≤h1<H, the density of the lithium-based ceramic material obtained by sintering the green body is greater than or equal to 99%;
[0079] The height h1 is the distance between the upper surface of a lithium-based ceramic green body and the lower surface of the lowest lithium-based ceramic green body.
[0080] In some embodiments, the particle size of the first lithium-based ceramic pre-fired powder is 0.5 to 5 mm; the particle size of the second lithium-based ceramic pre-fired powder is 20 to 80 μm.
[0081] In some embodiments, step S1 further includes: after laying a layer of second lithium-based ceramic pre-fired powder on the first lithium-based ceramic pre-fired powder, stacking a plurality of lithium-based ceramic green bodies along the thickness direction and placing them on the second lithium-based ceramic pre-fired powder.
[0082] In some embodiments, the first crucible, the second crucible, and the crucible cover are all made of magnesium oxide.
[0083] In some embodiments, the first lithium-based ceramic pre-fired powder and the second lithium-based ceramic pre-fired powder are independently obtained by the following methods:
[0084] Raw materials are provided according to the stoichiometric ratio of each element in the lithium-based ceramic material, wherein the raw materials include a lithium source, the mass of the lithium element in the lithium source is recorded as m, the theoretical amount of the lithium element is recorded as m0, and 1.1m0≤m≤1.2m0 is satisfied; the raw materials are then pre-fired at 800-1000°C and crushed to obtain lithium-based ceramic pre-fired powder.
[0085] In some embodiments, the lithium-based ceramic green body is obtained by the following method:
[0086] Raw materials are provided according to the stoichiometric ratio of each element in the lithium-based ceramic material, wherein the raw materials include a lithium source, the mass of the lithium element in the lithium source is recorded as m, the theoretical amount of the lithium element is recorded as m0, and 1.1m0≤m≤1.2m0 is satisfied; the raw materials are then pre-fired and crushed at 800-1000° C. to obtain lithium-based ceramic pre-fired powder; and the lithium-based ceramic pre-fired powder is then granulated and formed to obtain the lithium-based ceramic green body.
[0087] Compared with the prior art, the present invention has the following advantages:
[0088] 1. In this process, the use of alcohol solvents can disperse the slurry well, reduce the slurry viscosity during grinding and the particle size after sanding, and also make the grain size after pre-sintering smaller.
[0089] 2. In this process, the slurry is dried and then pre-fired directly, which eliminates the process of crushing after drying. Generally, the slurry will be dried and crushed before pre-fired. Crushing will cause the grains to connect after pre-fired and hinder the atmosphere removal during pre-fired. In this application, an alcohol solvent is used in combination with drying and then pre-fired directly; during the drying process, the state of the slurry can make the raw materials mixed evenly, and the raw material particle size is well dispersed, which is conducive to the independent particle size after the alcohol solvent evaporates at high temperature, so that the connection is reduced during pre-fired. If the particle size is connected to each other, material exchange will occur, resulting in the particle size being sintered during pre-fired, causing the grain to grow and reduce the sintering activity; and the pores between the particle size after the alcohol agent evaporates are conducive to the exclusion of atmosphere during pre-fired, and the existing pores further make the independent dispersed particle size not easy to produce material exchange during the subsequent high-temperature pre-fired process, avoiding the situation of grain connection, and the grains after pre-fired are well dispersed.
[0090] 3. When using alumina crucibles in the traditional way, some Al 3+ Conducted from the crucible to the lithium-based ceramic pre-sintered powder, a substitution reaction occurs with its lattice Al 3+ Replace Li + , causing aluminum contamination in the lithium-based ceramic pre-fired powder, affecting subsequent doping and test results; utilizing the inertness of the MgO crucible can reduce the reaction between the lithium-based ceramic pre-fired powder and the crucible, maintaining the purity of the lithium-based ceramic pre-fired powder, and not affecting subsequent doping and product performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0091] Figure 1 This is a particle size distribution diagram of the raw materials in the slurry after grinding in Example 3 of the present application.
[0092] Figure 2 This is a differential thermal gravimetric curve of the raw materials in Example 3 of the present application.
[0093] Figure 3 This is a scanning electron microscope image of the lithium-based ceramic pre-fired powder 2000X in Comparative Example 1 of this application.
[0094] Figure 4 This is a scanning electron microscope image of the lithium-based ceramic pre-fired powder 4000X in Comparative Example 1 of this application.
[0095] Figure 5 This is a scanning electron microscope image of the lithium-based ceramic pre-fired powder 2000X in Example 1 of the present application.
[0096] Figure 6 This is a scanning electron microscope image of the lithium-based ceramic pre-fired powder 4000X in Example 1 of the present application.
[0097] Figure 7 This is a scanning electron microscope image of the lithium-based ceramic pre-fired powder 2000X in Example 2 of the present application.
[0098] Figure 8This is a scanning electron microscope image of the lithium-based ceramic pre-fired powder 4000X in Example 2 of the present application.
[0099] Figure 9 This is a simulation diagram of the mechanism of sintering neck formation.
[0100] Figure 10 This is a scanning electron microscope image of the lithium-based ceramic pre-fired powder 2000X in Example 3 of the present application.
[0101] Figure 11 This is a scanning electron microscope image of the lithium-based ceramic pre-fired powder 4000X in Example 3 of the present application.
[0102] Figure 12 This is the XRD pattern of the lithium-based ceramic pre-fired powder in Example 3 of the present application. DETAILED DESCRIPTION
[0103] In order to make the purpose, technical solutions and advantages of this application more clear, the following further describes this application in detail with reference to the embodiments. It should be understood that the specific embodiments described herein are only used to explain this application and are not intended to limit this application.
[0104] Throughout this specification, reference to terms such as "one embodiment," "some embodiments," "illustrative embodiments," "examples," "specific examples," or "some examples" means that a specific feature, structure, material, or characteristic described in conjunction with an embodiment or example is included in at least one embodiment or example of the present application. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more embodiments or examples.
[0105] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of the technical features being referred to. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of such features. Throughout the description of this application, "plurality" means at least two, for example, two, three, etc., unless otherwise specifically defined.
[0106] In the production process of lithium-based ceramics, the pretreatment of raw materials is one of the key factors in the preparation of high-quality solid electrolyte materials. Lithium-based ceramic pre-fired powder has a great influence on the performance of lithium-based ceramic materials obtained by subsequent sintering. If the pre-fired reaction of the raw materials is incomplete, the lithium-based ceramic material will still undergo an incomplete pre-fired reaction before reaching the sintering temperature, exhausting the gas, resulting in more pores and low density in the sintered lithium-based ceramic material.
[0107] If the grains in the lithium-based ceramic pre-fired powder are coarse, it means that the raw materials have undergone physical and chemical reactions during the sintering process during the pre-fired stage, and have lost some of their sintering activity, which overlaps with the sintering process and easily causes over-sintering during the sintering process. As a result, the grain size distribution of the sintered lithium-based ceramic material is uneven, there are many pores, and the density is low. After being used as a solid electrolyte to assemble into a battery, it has poor stability to lithium. Lithium dendrites are easily generated between the grains and in the pores, destroying the intercrystalline bonding force and electrolyte strength of the electrolyte, causing the electrolyte to break easily during use, thereby reducing its service life.
[0108] When preparing solid lithium-based ceramic pre-fired powder, selecting appropriate raw materials, solvents, grinding equipment, grinding time, and pre-fired process can make the pre-fired powder particles small, uniform, and well dispersed, which can greatly improve the grain size distribution of the solid electrolyte after sintering, reduce porosity, increase bending strength, and improve lithium stability and service life.
[0109] In addition, LLZO in lithium-based ceramic materials has high ionic conductivity and is stable to lithium metal, and can be used as a solid electrolyte. LLZO generally has two phases, tetragonal phase (t-LLZO) at room temperature and cubic phase (c-LLZO) after 800℃. The ionic conductivity of the tetragonal phase is relatively low, generally only 10 -6 S / cm, while the cubic phase can reach 10 -4 In order to keep LLZO in cubic phase at room temperature, it is usually doped with high-valence Zr cations, such as Ta, Nb, W, Ti, etc., and sintered at 920°C.
[0110] This application proposes a method for preparing a pre-fired lithium-based ceramic powder. The overall concept is to utilize the dispersive grinding properties of alcoholic solvents to prevent fragmentation after drying, allowing the dried powder to remain dispersed and independent in a slurry state. Pre-fired, the pre-fired grains are small and unconnected, thus exhibiting good sintering activity.
[0111] For specific technical implementation, please refer to the method described in Example 1 below.
[0112] In some examples, the steps are as follows:
[0113] (1) Prepare raw materials: Li source, La source, Zr source, Ta source, according to the chemical formula Li 7-x La3Zr 2-x Ta x O 12 , adding a high-purity alcohol solvent, preferably 99% ethanol, to make the raw materials into a slurry;
[0114] Where 0.4≤x≤0.8, preferably x=0.6,
[0115] The Li source is one of lithium carbonate, lithium nitrate, and lithium hydroxide, preferably lithium carbonate. The La source is one of lanthanum oxide, lanthanum hydroxide, and lanthanum nitrate, preferably lanthanum hydroxide. The Zr source is one of zirconium oxide, zirconium hydroxide, and zirconium nitrate, preferably zirconium oxide. The Ta source is one of tantalum oxide, tantalum hydroxide, and tantalum nitrate, preferably tantalum oxide.
[0116] The mass ratio of the solid material to the alcohol solvent is 0.2 to 0.8:1, preferably 0.4 to 0.5:1.
[0117] (2) Sand milling: Mix the slurry with ethanol and then sand mill (sand milling ensures that the particle size of the raw materials is submicron). The sand mill speed is 2000 rpm. After sand milling for a certain period of time, remove the slurry.
[0118] (3) Drying: Pour the slurry into a MgO crucible and place it in an oven for a period of time. The insulation temperature is 70°C to 90°C, preferably 80°C, and the insulation time is 600min to 800min, preferably 720min.
[0119] The drying process is to dry the ethanol to form a loose and porous structure, and to prevent the ethanol concentration in the air in the pre-firing furnace from being too high, causing an explosion at high temperature.
[0120] (4) Pre-firing: Take out the dried crucible and place it in a pre-firing furnace, raise the temperature to 400°C and keep it for 60min-480min, raise it to 650°C and keep it for 60min-480min, then raise it to 720°C and keep it for 60min-480min, then raise it to 770°C and keep it for 60min-480min, then raise it to 920°C and keep it for 300min-600min; the heating rate is 5°C / min.
[0121] The scheme of the present application is described below with reference to the following specific examples. Unless otherwise specified, the raw materials used in the following examples are all from common commercial products, and the devices or equipment used are all purchased from conventional market sales channels.
[0122] Comparative Example 1
[0123] (1) preparing raw materials: Li source with n(Li2CO3)=3.84, n(La(OH)3)=3, n(ZrO2)=1.4, n(Ta2O5)=0.3, mixed in a mass ratio of m(material):m(ethanol)=3:7 to form a slurry;
[0124] (2) Sand grinding: The slurry was sand ground for 3 h using a sand grinder, and the particle size of the powder was Dv50 = 0.425 μm;
[0125] (3) Drying: Pour the slurry into a MgO crucible with a slurry thickness of 10 mm;
[0126] (4) Pre-calcination treatment: Place the crucible containing the slurry in an oven and keep it at 80°C for 720 minutes to dry it, and crush the powder with a crusher;
[0127] (5) Pre-firing: The dried crucible is taken out and placed in a pre-firing furnace, and the temperature is directly raised from room temperature to 920°C and kept for 720 minutes; the heating rate is 5°C / min, and lithium-based ceramic pre-firing powder is obtained.
[0128] The scanning electron microscope images of the lithium-based ceramic pre-sintered powder obtained above at different magnifications are as follows: Figure 3 and Figure 4 As shown, through Figure 3 and Figure 4 It can be seen that the crushed pre-sintered powder has serious grain connection, the grain size is about 20μm, and the powder reaction is incomplete.
[0129] Example 1
[0130] (1) Li source: n(Li2CO3) = 3.84, n(La(OH)3) = 3, n(ZrO2) = 1.4, n(Ta2O5) = 0.3, mixed in a mass ratio of m(material): m(ethanol) = 3:7 to prepare a slurry;
[0131] (2) Sand grinding: The slurry was sand ground for 3 hours using a sand grinder. The particle size Dv50 of the powder was 0.417 μm.
[0132] (3) Slurry: Pour the slurry into a magnesium oxide crucible with a slurry thickness of 10 mm;
[0133] (4) Pre-firing treatment: Place the crucible containing the slurry in an oven at 80°C for 720 minutes for drying;
[0134] (5) Pre-firing: The dried crucible is taken out and placed in a pre-firing furnace, and the temperature is directly raised from room temperature to 920°C and kept for 720 minutes at a heating rate of 5°C / min to obtain lithium-based ceramic pre-firing powder.
[0135] The scanning electron microscope images of the lithium-based ceramic pre-sintered powder obtained above at different magnifications are as follows: Figure 5 and Figure 6 As shown, through Figure 3 、 4 and Figure 5 、 6 It can be seen from the comparison that when pre-sintering without damaging the powder, the grain connection is improved, but it does not completely disappear; the grain size is reduced to about 5μm~10μm, and some powder reactions are incomplete.
[0136] Example 2
[0137] (1) preparing raw materials: Li source with n(Li2CO3)=3.84, n(La(OH)3)=3, n(ZrO2)=1.4, n(Ta2O5)=0.3, mixed in a mass ratio of m(material):m(ethanol)=3:7 to form a slurry;
[0138] (2) Sand grinding: The slurry was sand ground for 3 hours using a sand grinder, and the particle size of the powder was Dv50 = 0.409 μm.
[0139] (3) Slurry: Pour the slurry into a magnesium oxide crucible with a slurry thickness of 10 mm;
[0140] (4) Pre-firing treatment: Place the crucible containing the slurry in an oven at 80°C for 720 minutes for drying;
[0141] (5) Pre-firing: Take out the dried crucible and place it in a pre-firing furnace, raise the temperature to 400°C and keep it for 120 minutes, raise the temperature to 650°C and keep it for 120 minutes, then raise the temperature to 720°C and keep it for 120 minutes, then raise the temperature to 770°C and keep it for 120 minutes, and then raise the temperature to 920°C and keep it for 720 minutes; the heating rate is 5°C / min.
[0142] The scanning electron microscope images of the lithium-based ceramic pre-sintered powder obtained above at different magnifications are as follows: Figure 7 and Figure 8 As shown, through Figure 5 、 6 and Figure 7 、 8 It can be seen from the comparison that heat preservation treatment at the above temperature point will further improve the connection of grains, the grains are independently dispersed, and the powder reaction is complete, but sintering necks appear between the grains, and several small grains grow into large grains. The grain size after growth is about 3μm to 5μm. Among them, the mechanism simulation diagram of the formation of sintering necks is shown in the figure below. Figure 9 As shown in the figure, the formation of sintering neck indicates that the raw materials have been partially sintered. At this time, the pre-burning stage has passed and the sintering process has entered the middle and late stages. This is harmful to the later sintering process. Figure 8 It can be clearly seen that sintering necks appear between almost all small grains to form pores, and several small grains are fused into larger grains.
[0143] Example 3
[0144] (1) preparing raw materials: Li source with n(Li2CO3)=3.84, n(La(OH)3)=3, n(ZrO2)=1.4, n(Ta2O5)=0.3, mixed in a mass ratio of m(material):m(ethanol)=3:7 to form a slurry;
[0145] (2) Sand grinding: The slurry was sand ground for 3 hours using a sand grinder, and the particle size of the powder was Dv50 = 0.433 μm.
[0146] (3) Slurry: Pour the slurry into a magnesium oxide crucible with a slurry thickness of 10 mm;
[0147] (4) Pre-firing treatment: Place the crucible containing the slurry in an oven at 80°C for 720 minutes;
[0148] (5) Pre-firing: Take out the dried crucible and place it in a pre-firing furnace, raise the temperature to 400°C and keep it for 120 minutes, raise the temperature to 650°C and keep it for 120 minutes, then raise the temperature to 720°C and keep it for 120 minutes, then raise the temperature to 770°C and keep it for 120 minutes, and then raise the temperature to 920°C and keep it for 480 minutes; the heating rate is 5°C / min.
[0149] The scanning electron microscope images of the lithium-based ceramic pre-sintered powder obtained above at different magnifications are as follows: Figure 10 and Figure 11 As shown, through Figure 7 、 8 and Figure 10 、 11 It can be seen from the comparison that when the holding time at 920℃ is reduced, there is no connection between the grains, no sintering neck, and the grain size is between 1μm and 3μm.
[0150] The XRD pattern of the lithium-based ceramic pre-fired powder obtained above is as follows: Figure 12 As shown in the figure, by comparing with the XRD card of c-LLZTO, it can be seen that the obtained lithium-based ceramic pre-fired powder is a cubic garnet phase electrolyte, indicating that Ta doping enables the lithium-based ceramic to maintain a cubic phase at room temperature, and also indicates that the pre-fired reaction is fully carried out. Combined with its smaller grain size, the lithium-based ceramic pre-fired powder has good sintering activity.
[0151] Example 4
[0152] This embodiment is similar to embodiment 1, and the details are as follows:
[0153] (1) Li source: n(Li2CO3) = 3.84, n(La(OH)3) = 3, n(ZrO2) = 1.4, n(Ta2O5) = 0.3, mixed in a mass ratio of m(material): m(ethanol) = 2:7 to prepare a slurry;
[0154] (2) Sand grinding: The slurry was sand ground for 3 hours using a sand grinder. The particle size Dv50 of the powder was 0.306 μm.
[0155] (3) Slurry: Pour the slurry into a magnesium oxide crucible with a slurry thickness of 8 mm;
[0156] (4) Pre-firing treatment: Place the crucible containing the slurry in an oven at 90°C for 600 minutes to dry;
[0157] (5) Pre-firing: The dried crucible is taken out and placed in a pre-firing furnace, and the temperature is directly raised from room temperature to 920°C and kept for 720 minutes at a heating rate of 5°C / min to obtain lithium-based ceramic pre-firing powder.
[0158] Similar to the pre-burned powder obtained in Example 1, direct pre-burning without damaging the powder improved the grain connection, but did not completely disappear; the grain size was reduced to about 5μm to 10μm, but some powder still had incomplete reaction.
[0159] Example 5
[0160] (1) preparing raw materials: Li source with n(Li2CO3)=3.84, n(La(OH)3)=3, n(ZrO2)=1.4, n(Ta2O5)=0.3, mixed in a mass ratio of m(material):m(ethanol)=4:6 to form a slurry;
[0161] (2) Sand grinding: The slurry was sand ground for 3 hours using a sand grinder. The particle size Dv50 of the powder was 0.489 μm.
[0162] (3) Slurry: Pour the slurry into a magnesium oxide crucible with a slurry thickness of 10 mm;
[0163] (4) Pre-firing treatment: Place the crucible containing the slurry in an oven at 70°C for 800 minutes;
[0164] (5) Pre-firing: Take out the dried crucible and place it in a pre-firing furnace, raise the temperature to 400°C and keep it for 80 minutes, raise the temperature to 650°C and keep it for 80 minutes, then raise the temperature to 720°C and keep it for 80 minutes, then raise the temperature to 770°C and keep it for 80 minutes, and then raise the temperature to 920°C and keep it for 350 minutes; the heating rate is 5°C / min.
[0165] The grain size of the lithium-based ceramic pre-fired powder obtained above is reduced to about 3-5 μm, and the grain connection is improved, but it has not completely disappeared. This may be due to insufficient decomposition temperature period, and the previous decomposition temperature period is still in progress after reaching the pre-fired temperature period, or the powder is not completely decomposed after the pre-fired period, which may cause the powder to still have some connection after pre-fired (similar to Figure 6 is relatively similar).
[0166] Example 6
[0167] (1) preparing raw materials: Li source with n(Li2CO3)=3.84, n(La(OH)3)=3, n(ZrO2)=1.4, n(Ta2O5)=0.3, mixed in a mass ratio of m(material):m(ethanol)=3:7 to form a slurry;
[0168] (2) Sand grinding: The slurry was sand ground for 3 hours using a sand grinder. The particle size Dv50 of the powder was 0.423 μm.
[0169] (3) Slurry: Pour the slurry into a magnesium oxide crucible with a slurry thickness of 10 mm;
[0170] (4) Pre-firing treatment: Place the crucible containing the slurry in an oven at 85°C for 700 minutes to dry;
[0171] (5) Pre-firing: Take out the dried crucible and place it in a pre-firing furnace, raise the temperature to 400°C and keep it for 480 minutes, raise it to 650°C and keep it for 480 minutes, then raise it to 720°C and keep it for 480 minutes, then raise it to 770°C and keep it for 480 minutes, and then raise it to 920°C and keep it for 550 minutes; the heating rate is 5°C / min.
[0172] The crystal grains of the lithium-based ceramic pre-fired powder obtained above are free of connection and sintering neck, and the crystal grain size is between 1 μm and 3 μm.
[0173] Example 7
[0174] The difference between this embodiment and embodiment 3 is that:
[0175] (IV) Pre-calcination treatment: The crucible containing the slurry was placed in an oven at 70°C for 480 minutes. It was found that the ethanol was not evaporated and a loose and porous structure could not be effectively formed. The subsequent high-temperature pre-calcination would produce more ethanol, which would pose a safety problem.
[0176] It can be seen from the above examples and comparative examples that:
[0177] 1) After mixing the abrasive, drying and direct pre-sintering can significantly improve the bonding of the pre-sintered powder grains and reduce the grain size to about 5μm to 10μm, but there will still be incomplete powder reaction;
[0178] 2) Staged pre-sintering can further improve the connection of the grains, making the powder reaction more complete, reducing the particle size to about 3-5μm, and the morphology more ideal, but there may still be some pores formed by sintering necks, or partial connection;
[0179] 3) Furthermore, during the staged pre-sintering process, the pre-sintering holding time of the first few stages is controlled to be between 120 and 480 minutes, and the holding time corresponding to the highest temperature is between 300 and 600 minutes. The pre-sintering effect is ideal, with no connection between the grains, no sintering necks, and a grain size between 1 μm and 3 μm.
[0180] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent replacements and improvements made within the principles of the present application should be included in the scope of protection of the present application.
Claims
1. A method for preparing lithium-based ceramic pre-sintered powder, characterized in that: The following steps are involved: Step S1: providing raw materials according to the stoichiometric ratio of lithium-based ceramics; Step S2: mixing the raw materials with an alcohol solvent and grinding them to obtain a slurry; Step S3: directly pre-sintering the slurry after drying to obtain lithium-based ceramic pre-sintered powder.
2. The method according to claim 1, characterized in that In the step S1, the lithium-based ceramic is selected from any one of the substances shown in Formula 1; Li 7-x La3Zr 2-x M x O 12 Formula 1 Wherein, M is a doping element, and M is selected from at least one of Ta, Nb, W, and Ti, preferably Ta; The value range of x is: 0.4≤x≤0.8, preferably 0.6; Preferably, the raw material includes a lithium source, the mass of the lithium element in the lithium source is denoted as m, and the theoretical amount of the lithium element is denoted as m0, satisfying 1.1m0≤m≤1.2m0.
3. The method according to claim 1, characterized in that In step S2, the alcohol solvent includes at least one of methanol, ethanol, and propanol; The mass ratio of the raw material to the alcohol solvent is 0.2-0.7:
1.
4. The method according to claim 1, characterized in that: In the step S2, the Dv50 of the raw materials in the slurry is below 0.5 μm.
5. The method according to claim 1, characterized in that In the step S3, the step of directly pre-firing the slurry after drying it comprises: placing the slurry in a magnesium oxide crucible for drying and then directly pre-firing it; Preferably, the drying conditions include: drying temperature: 70° C. to 90° C.; drying time: 600 min to 800 min.
6. The method according to claim 5, characterized in that In the step S3, the liquid level of the slurry in the magnesium oxide crucible does not exceed 10 mm.
7. The method according to any one of claims 1 to 6, characterized in that: In step S3, the conditions of the pre-burning treatment include: heating to 390-410°C and keeping warm for 60-550 minutes, then heating to 640-660°C and keeping warm for 60-550 minutes, then heating to 710-730°C and keeping warm for 60-550 minutes, then heating to 760-770°C and keeping warm for 60-550 minutes, then heating to 910-930°C and keeping warm for 300-800 minutes; Preferably, in step S3, the conditions for the pre-burning treatment include: heating to 390-410°C and keeping warm for 120-480 min, then heating to 640-660°C and keeping warm for 120-480 min, then heating to 710-730°C and keeping warm for 120-480 min, then heating to 760-770°C and keeping warm for 120-480 min, then heating to 910-930°C and keeping warm for 300-600 min.
8. The method according to claim 7, characterized in that The heating rates in the pre-calcination treatment are independently 3 to 10° C. / min.
9. A lithium-based ceramic pre-fired powder, characterized in that: Prepared according to the method according to any one of claims 1 to 8; the grain size of the lithium-based ceramic pre-sintered powder is 0.1 to 10 μm, preferably 1 to 3 μm.
10. A method for preparing a lithium-based ceramic material, characterized in that: The invention comprises the method for preparing lithium-based ceramic pre-sintered powder as described in any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method for aluminum-containing cubic-phase garnet Li7La3Zr2O12
CN109319837A
Preparation method and application of garnet type solid electrolyte
CN115275329A
Graphite composite material and battery negative electrode and battery using same
CN116053481A
Preparation method of large-size lithium lanthanum zirconium tantalum oxide solid electrolyte
CN118754660A
Manufacture of positive electrode for nonaqueous secondary battery
JP2000012024A